Mathematics applied principles and methodologies - Bech, Lawrence (Wiilford Press, 2018)
Mathematics is the science of numbers, space, change and structures. Modern theories and methods of mathematics are applied in fields such as engineering, computer science, etc. Applied mathematics finds connections between mathematics and other disciplines to contribute to the better understanding of mathematical laws and methods. This book is a compilation of chapters that discuss the most vital concepts and emerging trends in the field of mathematics. Coherent flow of topics, student-friendly language and extensive use of examples make this book an invaluable source of knowledge.